Pengembangan materi ajar mata kuliah Apresiasi Drama melalui penggalian nilai-nilai pendidikan karakter naskah drama Panembahan Reso karya W.S. Rendra - Suryanto, Edy (citeus, 2016)
The purpose of this study is to describe the values of character education to develop teaching and learning materials for Drama course. It is a qualitative descriptive study by using Research and Development design. The data were obtained from the play entitled Panembahan Reso¸ written by W.S. Rendra by looking at the settings, the characters, the plots and some relevant documents. The technique used to collect the data was by document analysis technique. The results of the data analysis using interactive data analysis indicate that the values of character education are reflected throught the characters and their characterization; the values represented include the attitudes of being religious, hard working, peaceful, democratics, caring, fond of reading, responsible, having national spirit and excellence recognition.